EMOSITIONAL BRANDING PARFUME HMNS TERHADAP BRAND LOYALTY PELANGGAN - Listiani, Endri; Robiah, Siti; Umarella, Farid Hamid (Gapenas Publisher, 2024)
The perfume business trend has been increasing in recent years. Establishing the existence of our products with brands that are known in the community is something important. By utilizing emotional branding is a phenomenon that is taken to build a strong relationship between brands and consumers as with HMNS perfume. Through strong and consistent marketing communications, the HMNS perfume brand conducts a dialogue with their consumers. By utilizing emotional branding, HMNS perfume competes with many local perfume companies competitively to gain brand loyalty from customers. In this study, the researcher tested the influence of emotional branding on customer brand loyalty. This study aims to determine how much influence emotional branding has on customer brand loyalty. This study uses a quantitative method, with a survey of customers and distributing questionnaires to answer research questions. The number of samples in this study was 82 people. The data collection techniques used were questionnaires and interviews. The results of the study showed that: 1. emotional branding variables have a positive effect on customer brand loyalty. 2. Simultaneously, emotional branding (relationships, sensory experiences, imagination and vision) have an effect on customer brand loyalty